Response of Barley (Hordeum vulgare L.) Growth, Yield, and Crop Components to Irrigation Frequency and Salicylic Acid Concentrations - Raheem Bohan Al-Nasr-Allah; Muaid Shaker Ali; Dunya Sabeeh Mohammed (Universitas Sebelas Maret, 2026)
The irrigation regime is one of the primary factors limiting barley productivity. This study aimed to investigate the effect of salicylic acid on barley performance under varying irrigation conditions. A field experiment was conducted during the winter season of 2024 to 2025 using a split-plot design arranged in a randomized complete block design (RCBD) with 3 replicates. Irrigation frequency (3, 4, and 5 times during the growing season) was assigned to the main plots, while salicylic acid concentrations (0, 100, 200, and 300 mg l-1) were distributed to the subplots. The studied traits included the number of tillers per plant, plant height, flag leaf area, relative water content of leaf, absolute growth rate, biomass duration, 100-grain weight, number of grains per spike, and grain yield. The results showed that increasing irrigation frequency positively enhanced all studied traits except relative water content, with the 5-irrigation treatment resulting in the highest grain yield (1.383 kg m-2). Spraying salicylic acid at a concentration of 300 mg l-1 considerably improved most growth and yield traits, with the highest grain yield (1.370 kg m-2), compared with the control treatment, which recorded the lowest grain yield (0.959 kg m-2). Strong positive correlations were observed among biomass accumulation, yield components, and grain yield. The combined application of 5 irrigations and 300 mg l-1 of salicylic acid resulted in the highest grain yield (1.668 kg m-2). These findings suggest that appropriate irrigation management combined with salicylic acid during barley development can be an effective strategy to enhance barley productivity.